Evaluation of occupational safety and health policies in Malaysia / Au Yong Hui Nee - Au Yong, Hui Nee (2010)
The initial Occupational Safety and Health (OSH) legislation in Malaysia was constructed by the British administration. Malaysia continued to improve the legislation's scope to ensure that it continues to support the nation's growth. Workers in the warehousing and storage industry or third party logistic providers in some cases suffer high rate of occupational accidents as reflected in considerable share of occupational fatalities and lost-time injuries. OSH of workers should be integrated into the management plans so as to yield the benefits of high efficiency workforce. The main OSH national policy in Malaysia is the enactment of Factories and Machinery Act (FMA) 1967 and Occupational Safety and Health Act (OSHA) 1994. Other legislation was also formulated to address specific issues and concerns. This paper reviews their implementation and various impacts on OSH in Malaysia. Data were obtained from official sources. This paper discusses the current OSH status of warehousing and storage industry. The OSH problems are tied largely to the companies' organization and how the work is performed. Occupational accidents happened which resulted from many factors including poor OSH management system, inadequacies in access to information, inadequate training of personnel, machinery was not provided with appropriate tools and improper adoption of personal protective equipment, while the employees lacked awareness and knowledge of OSH and emergency response. Recommendations to improve OSH level are discussed in the paper. Potential solutions are such as enhancement in labor-management OSH planning and management, training of employees, adoption of new technologies, up-to-date regulation, and continuous health monitoring.